An Annotated Atlas of the Freshwater Fishes of North Carolina - Bryn H. Tracy; Fred C Rohde; Gabriela M Hogue (Southeastern Fishes Council Proceedings, 2020)
North Carolina’s first state-specific checklist of freshwater fish species was published in 1709 by John Lawson. Subsequent species lists with descriptions included: Brickell (1737), Cope (1870a), Jordan (1889a), Jordan and Evermann (1896-1900), Smith (1907), Jordan et al. (1930), Fowler (1945), Louder (1962), Ratledge et al. (1966), Menhinick et al. (1974). In 1991, Menhinick published “The Freshwater Fishes of North Carolina”, which is still widely in use because a comprehensive update has not been produced since its publication. The increase in the availability of historical records in globally accessible databases and the surge of collections post-1991 made by federal and state resource agencies, and academic and museum researchers, allowed for the creation of an update of North Carolina’s freshwater fish species in an annotated atlas. Herein we discuss the distribution of the 257 currently described and undescribed freshwater fish species within North Carolina. Annotations for each species include a distributional map with type locality noted where appropriate, remarks concerning questionable records and misidentifications, extirpations, introductions and interbasin transfers, and imperilment status.
Keywords: North Carolina; Freshwater Fishes; Atlas; Distribution; Indigenous; Nonindigenous